THE DELUSION OF BEING HUMAN: FANTASTIC MOTIVES IN THE MOVIE ANOMALISA (2015) BY CHARLIE KAUFMAN AND DUKE JOHNSON - Azmi Kartika Sari (IJLECR (International Journal of Language Education and Cultural Review), 2019)
This study aims to analyze the fantastic motives that lay inside a movie titled Anomalisa. The background of choosing this movie as an object is caused by the unique concept where all the other characters except the main character named Michael have the same face and the same voice, no matter what gender they are. However, there is one exception which when Michael met a girl named Lisa, who is the only person ever in Michael’s world to ever has a different voice and face. This leads to a problem statement; whether the phenomenon of facial and voice uniformity is a fantastic event that is experienced directly by the character due to external factors or internal factor such as psychological intervention. This study uses qualitative method and in order to answer this question, the writer uses Todorov’s fantastic theoretical framework. The results show that the fantastic motives presented in Anomalisa is included in the fantastic uncanny category. The fantastic motives are present due to the delusion of Fregoli experienced by the main character, Michael Stones. Delusions experienced by Michael according to the author are triggered by a sense of boredom and loneliness experienced by Michael. Key words: Anomalisa; Fantastic literature; Film analysis; Tzvetan Todorov